Basal cell carcinoma of the prostate with squamous metaplasia: A case report and literature review - Wang, Junwei; Zhang, Cunming; Chen, Baijun; Wu, Qingqing (Frontiers in Oncology, 2023)
Basal cell carcinoma of the prostate (BCCP) is a rare tumor with a total incidence of 140 cases to date. However, BCCP with squamous metaplasia has not been reported. We report the first case of BCCP with squamous metaplasia. The patient was hospitalized for progressive dyspareunia. The patient was treated for recurrent urinary retention four times in 5 years. The rectal examination showed that the prostate was medium in texture with no palpable nodules. The levels of tPSA, fPSA, and f/t were 1.29 ng/mL, 0.4 ng/mL, and 0.31, respectively. Ultrasound of the urinary tract showed that the prostate gland was 51 mm*40 mm*38 mm in size. We performed transurethral electrodesiccation of the prostate. Histopathology confirmed it as basal cell carcinoma with focal squamous differentiation and immunohistochemical staining reported positive P63 and 34βE12 markers. A laparoscopic radical prostatectomy was performed 45 days after the first surgery and the postoperative pathology showed a small amount of residual tumor with no bilateral involvement of the seminal vesicles and vas deferens with negative margins. The patient was followed up for 50 months and he survived well. We describe the clinical symptoms, pathological features, treatment, and prognosis of patients with BCCP with squamous metaplasia. The relevant published literature is also briefly reviewed.